LEGITIMIZING CLAIMS FOR ‘CRISIS’ LEADERSHIP IN GLOBAL GOVERNANCE. - Schnurr, Stephanie; Homolar, Alexandra; MacDonald, Malcolm N.; Rethel, Lena (Critical Discourse Studies, 2015)
This paper explores the discursive processes of legitimizing leadership claims in the context of the nuclear proliferation crisis. Three complementary analyses of texts are carried out: discourse analyses of United Nations Security Council (UNSC) resolutions and relevant speeches by members of the US administration, as well as a corpus analysis of news media accounts of nuclear proliferation published in prominent US and UK broadsheets. Findings suggest that leadership claims are legitimized through a range of discursive strategies, which are echoed across the different text types. However, a combination and comparison of the different datasets puts these findings into perspective and reveals that the various contexts and text types in which these leadership claims are made differ remarkably in terms of their use of relevant terms relating to leadership and crisis. We argue that this dynamic is best captured by the notion of an (inter)discursive chain of legitimization.